Pengaruh Kualitas Rumah dan Lingkungan terhadap Kepuasan Penghuni dan Kecenderungan Berpindah di Perumnas Bukit Sendangmulyo Semarang - Widiastomo, Yudhi (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
This study aims to examine the influence of the quality of the house and environment on resident’s satisfaction and propensity to move at Bukit Sendangmulyo Housing. This research uses a quantitative approach through questionnaires and field observations. The analysis use descriptive statistical analysis and the analysis of SEM (Structural Equation Modeling). The result of the study show that the environmental quality has a significantly greater effect on resident’s satisfaction in Bukit Sendangmulyo Housing with estimated value 0.740, and for the quality of the house has a small effect on resident’s satisfaction with the estimated value 0.231. Resident’s satisfaction has a negative effect on the propensity to move with the estimated value -0.420. Therefore, the environment quality becomes the most important factor in the quality of living than the quality of the house and need to be noticed in the future development of social housing. The existence of the environment with good and complete infrastructure will make communities comfortable to stay so their propensity to move will be smaller.